Shop drawing of revised plan for 3rd storey, 4th storey & 5th storey SF11-SF12 (RFA-015_Rev C) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.